Progressive Gray Matter Loss and Changes in Cognitive Functioning Associated With Exposure to Herpes Simplex Virus 1 in Schizophrenia: A Longitudinal Study - Prasad, Konasale M.; Eack, Shaun M.; Goradia, Dhruman; Pancholi, Krishna M.; Keshavan, Matcheri S.; Yolken, Robert H.; Nimgaonkar, Vishwajit L. (The American journal of psychiatry, 2011)
Objective:Longitudinal changes in gray matter volume and cognitive performance were evaluated among individuals exposed to neurotropic herpes simplex virus subtype 1 (HSV1). There is a replicable association of HSV1 exposure with smaller prefrontal volumes and cognitive impairments in schizophrenia. Method:The authors concurrently examined the whole-brain longitudinal trajectory over 1 year of gray matter volumes and executive functioning measured with the Wisconsin Card Sorting Test among 26 first-episode antipsychotic-naive subjects with schizophrenia and 38 healthy subjects. Age, gender, socioeconomic status, and exposure to cytomegalovirus (another virus of the herpes family that was previously associated with cognitive impairments) were the covariates. Results:Significant gray matter loss in the posterior cingulate gyrus was noted among the HSV1-seropositive schizophrenia subjects over 1 year but not among other groups. Prefrontal gray matter volumes did not show longitudinal changes. Binomial mixed-effects models indicated that improvement over 1 year in Wisconsin Card Sorting Test categories completed and perseverative errors occurred in significantly fewer HSV1-seropositive schizophrenia subjects than in the HSV1-seronegative schizophrenia subjects or the healthy subjects regardless of serological status. Three-way interactions of diagnosis, HSV1 status, and time were significant for both categories completed and perseverative errors. An increase in perseverative errors over 1 year, but not the change in the number of categories completed, correlated with longitudinal volume loss of the posterior cingulate gyrus. Conclusions:These observations suggest that HSV1 exposure may be associated with longitudinal gray matter loss in the posterior cingulate gyrus and decline in executive functioning among subjects with schizophrenia.